Bacterial community analysis in three types of the fermented seafood, jeotgal, produced in South Korea. Issue 8 (3rd August 2018) - Song, Eun-Ji; Lee, Eun-Sook; Park, So-Lim; Choi, Hak-Jong; Roh, Seong Woon; Nam, Young-Do
ABSTRACT: Jeotgal is a traditional Korean seafood fermented by indigenous microbes. The bacterial community in five myeolchi - jeot ( Engraulis japonica ), five meongge - jeot ( Halocynthia roretzi ), and six saeu - jeot ( Acetes japonicas ) produced in South Korea was analyzed by barcoded pyrosequencing targeting the V1/V2 hyper-variable regions of the 16S rRNA gene. All samples were dominated by the phyla Firmicutes, which represented 67.7% (SD = 27.2%) of the population. Tetragenococcus halophilus and Tetragenococcus muriaticus were the predominant species in myeolchi - jeot . The LABs, Lactobacillus sakei, Lactobacillus curvatus, and Weissella koreensis were the predominant species in meongge - jeot . In myeolchi - jeot and meongge - jeot, the bacterial communities within samples were consistent in their predominance, however each of saeu - jeot samples had inter-individual variety in the bacterial community leading to the difficulties of standardization for the commercial production of saeu - jeot . The results of this study will conclusively help to expand our basic knowledge of jeotgal and the related microorganisms involved in food fermentation. Abstract : : Bacterial community analysis in three types of the Korean traditional fermented seafood, jeotgal.